A CLINICAL STUDY TO EVALUATE THE EFFICACY OF ASHWAGANDHADI YOGA IN THE MANAGEMENT OF SHWETA PRADARA W.S.R. TO LEUCORRHOEA (International Journal of Food and Nutritional Sciences, 2024)
Introduction-Vaginal discharge is a common feature that affects all age group of women worldwide. Shweta Pradara (white vaginal discharge) is defined as excessive secretion from the female reproductive tract especially from the vagina, cervix or both that can be equated with Leucorrhoea in Bio-medical Science. Recurrence of this condition is a common phenomenon making it a major concern worldwide. Material & Methods- The present clinical study was aimed to evaluate the efficacy of Ashwagandhadi Yoga mentioned in Siddha Yoga Sangreh in the management of Shweta Pradara. This single blind clinical study was conducted on 30 patients selected randomly from OPD & IPD of M.M.M Govt Ayurveda College ,Udaipur (Rajasthan). Ashwagandhadi Yoga in the dose of 2gm with Cow milk as Anupana for duration of 2 months was given to all the patients with follow up after every 15 days. The statistical analysis was done using Graph Pad Instat 3 and Mean Difference (MD), Standard Deviation (SD) and Standard Error (SE) of symptoms/variables were calculated for 30 patients. Results- Results showed statistically significant difference in the patients before and after the treatment with the trial drug. Conclusion- Ashwagandhadi Yoga can be used as an effective treatment modality for Shweta Pradara.